The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1007/s00421-011-2151-5
|View full text |Cite
|
Sign up to set email alerts
|

Postural stability of canoeing and kayaking young male athletes during quiet stance

Abstract: We studied the postural stability of 23 canoeing and kayaking young athletes and 15 healthy untrained age matched subjects during quiet and sensory conflicted stance (standing on stable and foam support with open and closed eyes). We measured with a force platform the center of pressure excursions and applied mean sway amplitude (MA), mean sway velocity (SV) and their Romberg ratios, and sway dispersion index to evaluate standing balance. During standing with eyes open, the athletes in comparison to non-athlet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 39 publications
2
30
0
1
Order By: Relevance
“…This is likely contributed by their training routines, which involve sensing the changing relations of the moving body and coordinating body musculature to maintain body balance. Individuals with active lifestyle, especially athletes were documented to have good body balance too [13]- [15]. Athletes exhibit smaller sway amplitude and sway velocity than non-athlete individuals.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is likely contributed by their training routines, which involve sensing the changing relations of the moving body and coordinating body musculature to maintain body balance. Individuals with active lifestyle, especially athletes were documented to have good body balance too [13]- [15]. Athletes exhibit smaller sway amplitude and sway velocity than non-athlete individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies also shown that postural stability in some sports e.g. soccer players, professional dancers, gymnasts and surfers, have strong visual dependence [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most related literature is a paper about postural stability of canoeing and kayaking young male athletes during quiet stance, pointed that affected by different sport character, the canoeing and kayaking athletes show different postural stability. Thus far there is no research about kayaking stability training being reported [52].…”
Section: Application Research Of Surface Electromyography (Semg) Techmentioning
confidence: 99%
“…None of the previous studies have investigated the coupling of postural sway to optic fl ow in sports expertise. Most of the studies have focused on identifying postural sway in a stable stance ( Aalto, Pyykkö, Ilmarinen, Kähkönen, & Starck, 1990 ;Golomer, et al ., 1999 ;Perrin, et al ., 2002 ;Schmit, Regis, & Riley, 2005 ) or postural characteristics by manipulating task constraints ( Mouchnino, et al ., 1992 ;Hugel, et al ., 1999 ;Vuillerme, Danion, et al ., 2001 ;Vuillerme & Nougier, 2004 ;Gautier, Thouvarecq, & Larue, 2008 ;Matsuda, et al ., 2008 ;Stambolieva, et al ., 2012 ). There has been only one study of postural adaptation to imposed optic fl ow in experienced gymnasts ( Gautier, Thouvarecq, & Vuillerme, 2008 ).…”
mentioning
confidence: 99%